(untitled) (Theatrum historiae, 2013)
The oldest sources documenting the life of St Elizabeth (1207–1231), which date back to the 13th century, created a strong tradition linking St Elizabeth with caring for the sick and ill. The mendicant movement brought forth a new understanding of the ill as the second Christ. The ill, as alter Christus, were the subject of Elizabeth’s charity. Sources originating from the period pertaining to Elizabeth’s life mention treatments of mainly infectious, highly repulsive diseases and the curing of corporeal defects, injuries and lethal injuries, in order to necessitate the biggest contrast and to excite awe in the recipients of the legends texts. Turning one’s soul away from sin was considered to be part of a person’s treatment, too. The physical shell of the ill wasn’t the final aim of her help. For Elizabeth, caring for the ill was a form of piety complementing her vita activa. The ill were to become one of the saint’s main attributes in art representation.